Reconstructing Islamic Education in the Modern Era: A Systematic Literature Review on Philosophical Foundations and Curriculum Challenges - Lelaini, Lelaini; Arisma, Sulastri; Atnelie, Mike; Muyanti, Tri; Anggraini, Gusti (PPSDP International Journal of Education, 2025)
This study aims to examine the philosophical foundations of Islamic education and their role in shaping individuals who are intellectually competent, morally upright, and socially as well as spiritually responsible. Using a Systematic Literature Review (SLR) approach, this research systematically identifies and analyzes academic literature related to the fundamental concepts, scope, and influence of Islamic education philosophy on curriculum development and the Islamic education system. The results show that Islamic education philosophy emphasizes the balance between intellectual, spiritual, and moral aspects as a unified framework in the educational process. The study also identifies major challenges in applying Islamic educational philosophical principles in the modern era, including educational dualism, the impact of globalization, and the insufficient integration of Islamic values within existing curricula. These findings imply the urgent need for reconstructing the Islamic education system to ensure its relevance to contemporary developments while maintaining its essential values. The novelty of this study lies in its updated synthesis of recent literature, which provides a comprehensive mapping of current philosophical discourse in Islamic education. Meanwhile, its contribution is reflected in offering a structured analytical foundation that educators, policymakers, and curriculum developers can use to design integrative and adaptive Islamic education curricula.